The Effectiveness of Free Vascularized Fibular Flaps in Osteonecrosis of the Femoral Head and Neck: A Systematic Review - Ligh, Cassandra A.; Nelson, Jonas A.; Fischer, John P.; Kovach, Stephen J.; Levin, L. Scott (Journal of Reconstructive Microsurgery, 2017)
Background Free vascularized fibular flaps (FVFFs) are accepted surgical options to treat osteonecrosis of the femoral head and neck (ONFHN) to prevent conversion to total hip replacement (THR), yet many studies are single institution cohorts, with little generalizability.Purpose The purpose of this study was to perform a systematic review examining the comparative effectiveness of FVFF to treat ONFHN, particularly preventing conversion to a THR and improving hip function/symptoms.Methods We searched PubMed and EMBASE databases using femoral head, free fibula, and femoral neck keywords. Articles were excluded if not translated into English, n < 10 hips, article was a compilation/review, outcomes were not relevant, or prior to 1994. If from the same institution, we included the largest cohort and excluded others within the same timeline. Two investigators independently reviewed articles and reported number of patients/hips, average age/follow-up time/graft survival before THR, Harris hip score, THR rate, complications, and radiographic progression rates.Results We identified 128 and 157 articles from PubMed and EMBASE. After screening/duplicate removal, 21 studies were included from 14 institutions in 9 countries. Overall, 71% were level IV evidence. The average patient number was 129, number of hips was 166, age at surgery was 34 years, and follow-up time was 92 months. HHS improved on average 21.7 points, with the number of patients requiring THR being 19.4%. Graft survival before THR was 5.2 years, and 47.7% of hips had radiographic progression.Conclusions There is a significant amount of level IV evidence describing the favorable role of FVFF to treat ONFHN. Although efficacious, there is a need for higher level evidence. The level of evidence is 3.
Keywords: osteonecrosis of the femoral head and neck; systematic review; free vascularized fibular flap